2002
DOI: 10.1081/cbi-120002878
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in effect of spa therapy on chronic pain

Abstract: This study sought to investigate whether the effects of spa therapy are subject to seasonal variation as suggested by conventional spa therapy research. A total of 268 female (age 31-90 yr) and 119 male (age 35-85 yr) patients with noninflammatory chronic pain were studied. Patients stayed at an Austrian spa for 3 wk and received 2-4 treatments per day, including mudpacks, massages, and exercise therapy. In different groups of patients for 2 yr, pain (self-assessed by questionnaire and Likert scales) and assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Strauss-Blasche et al conducted a monthly survey on mood and pains in 268 women who were treated for non-inflammatory chronic pains in the back and arthralgia at a hot spa clinic in Austria. 18 They reported improved mood and pain relief in spring and autumn, and that temperature, pain, and mood are interrelated. In the present study, both follow-up evaluations made in June and December demonstrated positive effects.…”
Section: Discussionmentioning
confidence: 99%
“…Strauss-Blasche et al conducted a monthly survey on mood and pains in 268 women who were treated for non-inflammatory chronic pains in the back and arthralgia at a hot spa clinic in Austria. 18 They reported improved mood and pain relief in spring and autumn, and that temperature, pain, and mood are interrelated. In the present study, both follow-up evaluations made in June and December demonstrated positive effects.…”
Section: Discussionmentioning
confidence: 99%
“…Second, due to organizational reasons, we had to split the entire IG as well as the vacation group into three subgroups each. Thus, there were seasonal variations (summer time/fall) regarding the 1-week stay at the health resort between the different subgroups and we did not control for potential seasonal effects on our studied outcomes [37]. Third, during recruitment we neither asked whether study applicants already had suffered from burnout syndrome nor controlled for depressive symptoms within the potential study population.…”
Section: Discussionmentioning
confidence: 99%
“…Strauss-Blasche et al (35) reported seasonal variation in the effects of spa therapy (including mud and CO 2 applications) on chronic pain. A total of 387 patients with non-inflammatory chronic pain stayed at a spa in Austria for 3 weeks and received 2-4 treatments per day, including mudpacks, massages, and exercise therapy.…”
Section: Non-inflammatory Diseasesmentioning
confidence: 99%